One-pot hydrothermal synthesis of porous nickel cobalt phosphides with high conductivity for advanced energy conversion and storage. (10th October 2016) - Hu, Yu-Mei; Liu, Mao-Cheng; Hu, Yu-Xia; Yang, Qing-Qing; Kong, Ling-Bin; Kang, Long
Graphical abstract: NixCo2-xP nanoparticles with high electrical conductivity were prepared through hydrothermal method, they show high specific capacity and excellent rate capability. Abstract: High electrical conductivity is a vital factor to improve electrochemical performance of energy storage materials. In this work, bimetallic nickel cobalt phosphides with high electrical conductivity and different Ni/Co molar ratios are directly fabricated via a simple hydrothermal method. The samples show uniform teeny nanoparticles morphology and excellent electrochemical performance. The NiCoP sample exhibits the most prominent specific capacity (571 C g −1 at 1 A g −1 ) and out-bound rate characteristic (72.8% capacity retention with a 20-fold increase in current densities), which can be attributed to the good crystallinity, larger specific surface area, and noteworthy intrinsic conductivity that convenient for fast electron transfer in active material and fleet reversible faradic reaction characteristics. Simultaneously, an optimal asymmetric supercapacitor based on NiCoP as positive and activated carbon as negative is assembled. It can achieve a high energy density of 32 Wh kg −1 (at a power density of 0.351 kW kg −1 ) and prominent cycling stability with 91.8% initial capacity retention after 3000 cycles. It demonstrates that nickel cobalt phosphides are promising as energy storage materials. The study could also pave the way to explore a new class of bimetallic phosphides materials high electrical conductivity for electrochemical energy storage.